2013
DOI: 10.1148/radiol.13122581
|View full text |Cite
|
Sign up to set email alerts
|

Markers of Good Performance in Mammography Depend on Number of Annual Readings

Abstract: Radiologists' determinants of performance are associated with annual reading volumes. Ability to recognize normal images is a discriminating factor in individuals with a high volume of mammographic readings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
82
3
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(98 citation statements)
references
References 23 publications
11
82
3
2
Order By: Relevance
“…Also, factors such as age, academic qualification or training, and number of years since qualification have been shown to influence accuracy of image interpretation. 11,12 While radiographers in the developed world acquire formal training in image interpretation, 4 there is no postgraduate training program in X-ray interpretation in Nigeria as yet. However, radiographers attain informal knowledge of image interpretation during practice through personal study, from radiologists, and other radiographers knowledgeable in X-ray interpretation.…”
mentioning
confidence: 99%
“…Also, factors such as age, academic qualification or training, and number of years since qualification have been shown to influence accuracy of image interpretation. 11,12 While radiographers in the developed world acquire formal training in image interpretation, 4 there is no postgraduate training program in X-ray interpretation in Nigeria as yet. However, radiographers attain informal knowledge of image interpretation during practice through personal study, from radiologists, and other radiographers knowledgeable in X-ray interpretation.…”
mentioning
confidence: 99%
“…In comparison, studies on breast radiologists have a reported JAFROC score of .79 12 . There may be a range of reasons for this outcome.…”
Section: Discussionmentioning
confidence: 99%
“…3b. Radiologists with higher expertise read more mammograms and have a better diagnostic performance [27]; hence, it is possible that they have a better idea as to what kinds of image appearance can cause difficulties in diagnosis. As a result, they may have chosen the areas more likely to cause interpretation problems as MD.…”
Section: Discussionmentioning
confidence: 99%